Matéria orgânica de um argissolo vermelho distrófico úmbrico após a introdução de fitofisionomias antrópicas - Soares, Julio Cesar Wincher (2011)
In the state of Rio Grande do Sul the expansion of forestry has been one of the major agents of landscape change, occupying land previously intended for livestock farming and agriculture with low technical level, in areas under the influence of the Pampa biome and the transition of this biome for the Atlantic Forest. There is a widespread belief about the negative impacts caused by forest plantations on natural resources. Thus, it is necessary to evaluate the impacts caused by the introduction of forest plantations on the landscape components, especially on the soil and organic matter. This study was performed to characterize the components of the landscape topography, vegetation cover and their relations with soil, as well as temporal variation in soillandscape Forestry Experiment Station, located in the central region of Rio Grande do Sul were also found, changes in inventory levels and nitrogen (N and SN) and organic carbon (CO and SCO) in profiles Typic Umbrian and the labile and stable organic matter in surface horizon of the soil under native forest at the intermediate stage regeneration and field man-made with over 35 years, mixed forest of Eucalyptus and Eucalyptus robusta 35, forest of Eucalyptus grandis with 4 and 21 years, forest of Acacia mearnsii at age 7, forest of Eucalyptus saligna and 6 years mixed forest with Pinus 10 years. The results indicated that there is a transitory components of the landscape between the edge of the Southern Rio Grande Plateau and the Central Depression of Rio Grande do Sul, as well, there is a characterization of the natural vegetation types and conflicts of land use. It was also found that the relief and the genesis of the soils were vegetational conditions for development and that in 22 years there have been expanding cultivation of Eucalyptus and Pinus and the native forest on the anthropic field, especially in lands with Argissolos Bruno-Acinzentados and Argissolos Vermelhos. The organic matter of Argissolo Vermelho distrófico úmbrico, the results suggest that the levels and stocks of nitrogen and organic carbon of their surface horizon, altered by the introduction of man-made forest and field areas of deciduous forest, with a decrease especially in land occupied by forest of Acacia mearnsii and field of human activity. In relation to the stocks of organic carbon and nitrogen in the soil profile had a greater influence of other factors and processes of soil formation than the occupation of land in the last four decades. We also observed changes in the distribution of particulate organic carbon (POC g.kg-1) in the surface horizon of the soil, and this organic matter fraction of a sensitive indicator of changes in land use and soil.